Regenerative plantlets with improved agronomic characteristics caused by anther culture of tetraploid potato (Solanum tuberosum L.) - Li Zhang; Feng-jie Nie; Lei Gong; Xiao-yan Gan; Guo-hui Zhang; Xuan Liu; Wen-jing Yang; Lei Shi; Yu-chao Chen; Rui-xia Xie; Zhi-qian Guo; Yuxia Song (PeerJ, 2023)
Objective As the primary means of plant-induced haploid, anther culture is of great significance in quickly obtaining pure lines and significantly shortening the potato breeding cycle. Nevertheless, the methods of anther culture of tetraploid potato were still not well established. Methods In this study, 16 potato cultivars (lines) were used for anther culture in vitro. The corresponding relation between the different development stages of microspores and the external morphology of buds was investigated. A highly-efficient anther culture system of tetraploid potatoes was established. Results It was shown in the results that the combined use of 0.5 mg/L 1-Naphthylacetic acid (NAA), 1.0 mg/L 2,4-Dichlorophenoxyacetic acid (2,4-D), and 1.0 mg/L Kinetin (KT) was the ideal choice of hormone pairing for anther callus. Ten of the 16 potato cultivars examined could be induced callus with their respective anthers, and the induction rate ranged from 4.44% to 22.67% using this hormone combination. According to the outcome from the orthogonal design experiments of four kinds of appendages, we found that the medium with sucrose (40 g/L), AgNO3 (30 mg/L), activated carbon (3 g/L), potato extract (200 g/L) had a promotive induction effect on the anther callus. In contrast, adding 1 mg/L Zeatin (ZT) effectively facilitated callus differentiation. Conclusion Finally, 201 anther culture plantlets were differentiated from 10 potato cultivars. Among these, Qingshu 168 and Ningshu 15 had higher efficiency than anther culture. After identification by flow cytometry and fluorescence in situ hybridization, 10 haploid plantlets (5%), 177 tetraploids (88%), and 14 octoploids (7%) were obtained. Some premium anther-cultured plantlets were further selected by morphological and agronomic comparison. Our findings provide important guidance for potato ploidy breeding.